AN ANALYSIS ON SPEAKING PROBLEMS IN SMP NEGERI 3 PEMATANG SIANTAR - Ligita Friskila Lumbantobing; Gebby Gabriella Simanjuntak; Liska Sinaga; Debora Hutajulu; Pani Santarika Saragih; Monira Noverdita Sinaga; Selviana Napitupulu (Universitas Pahlawan Tuanku Tambusai, 2022)
This study was aimed to find out the Speaking Problems at Seven Grade of SMP Negeri 3 Junior High School Pematangsiantar. This study used descriptive qualitative research method. The respondents of this study were Junior High School Students at Seven Grade of SMP Negeri 3 Junior High School Pematangsiantar. The objective of this research is to find out the students' problems in speaking skill. This research instruments were interview and observation. Based on the results of the observation and interview, the students have problem in speaking. The problems were consisted of poor in grammar, lack of vocabulary and meaning, pronunciation, lack of confident, fear of making mistake, shyness and anxiety. From the problems the dominantly problems is pronunciation, vocabulary, shyness. To overcome this problem, teachers need to use several ways or to have strategies such as using talking stick, role play, choosing interesting topic, etc. This research can facilitate the teachers in knowing the problems in speaking faced by the students. Keywords: Analysis, speaking, problems, talking stick